Prediction of spirometry parameters using chest circumference in Sri Lankan boys aged 8-16 years - Guwani Liyanage; Bernard Deepal Wanniarachchi Jayamanne (Journal of Health and Social Sciences)
Introduction: Most normative standards for spirometry are established based on height, weight and body mass index. We have investigated chest circumference as an alternative to height for interpretation when accurate height measurements cannot be obtained. Methods: This is a cross-sectional study conducted in Sri Lankan boys aged 8-16. Spirometry measurements were taken adhering to American Thoracic Society/European Respiratory Society 2005 recommendations. Data analysis was performed with SPSS Version 18 for Windows. Correlations (Pearson correlation coefficient) between lung volumes and chest circumference were evaluated. Subsequently, multiple regression analysis was performed between lung volumes and the predictor variables. Results: Six hundred and eighty-two (n = 682) boys with acceptable spirograms were included in the final analysis. Chest circumference was significantly correlated to height as well as spirometry parameters. Therefore, reference equations were established based on chest circumference and age. Discussion and Conclusions: Chest circumference could be considered as competent as height in predicting lung flows and volumes in Sri Lankan males aged 8 to 16, and it could be used as an alternative parameter in situations where height cannot be measured precisely.